Mapping research trends on PjBL-STEM in biology education and students’ 21st-century skills: A systematic literature review - Tutut Widiyaningsih; Baskoro Adi Prayitno; Meti Indrowati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: PjBL-STEM integration is increasingly being applied in biology learning at various levels of education, from primary school to university, in an effort to develop the 21st-century skills. Objectives: This study aims to provide in-depth information about the research landscape of the PjBL-STEM model in biology learning in terms of subject matter, the 21st-century skills, and learning media. Methods: This study used a systematic literature review with the PRISMA approach. Articles were obtained from Google Scholar and Scopus databases (2016–2025) using keywords related to PjBL-STEM, biology materials, and the 21st-century skills. A total of 19 articles met the inclusion criteria and were analyzed, with the distribution of educational levels including elementary school (5), junior high school (6), high school (7), and college (2), with one article covering more than one level. Results: The most frequently implemented materials were environmental pollution (4), biotechnology (3), and entomology, basic science, and metamorphosis (2 each). Meanwhile, the most dominant skills measured were creative thinking (10), critical thinking (9), collaboration (7), communication (4), and character building (1). The most widely used learning media were worksheets (8), followed by modules (2), and various other media such as learning videos, microscopes, 3D technology, Canvas web-based LMS, and interactive multimedia. Conclusion: The integration of PjBL-STEM into biology learning still emphasizes cognitive skill development over affective domains. These findings can serve as a strategic reference for educators and researchers to guide innovation and develop more adaptive PjBL-STEM learning in the future.